Tailoring Drug Release Kinetics by the Design and Optimization of Substituents in Azobenzene Molecules in the Photosensitive Liposomal System - Zhang, Yucheng (Langmuir : the ACS journal of surfaces and colloids, 2024)
A light-sensitive moiety, e.g., azobenzene, for the light-sensitive liposomal drug carrier has shown advantages as an advanced drug delivery system in site-specific smart therapy due to its reversible photoisomerization characteristics. In this work, a series of 4-position-cholesterol-functionalized azobenzene derivatives with 4'-position substituted pyridine, quinoline, isoquinoline, triethylamine, or ethylenediamine were synthesized, and the relationship between the molecular structure and drug release behaviors was clarified. We found that the charge and electrophilicity of substituents were two important factors (expressed as the characteristic time) that can precisely regulate the isomerization ratio in the liposomal system. There was an approximately linear correlation between the characteristic time of photoisomerization and the fitted first-order constant of photoinduced drug release rate. The photoinduced drug release could be achieved at the desired time and in an appropriate amount by tailoring the substituents at the 4'-position of azobenzene-cholesterol derivatives